The Indonesian Policy on the Export of Sea Sand on Economy and Coastal Communities - Hidayat, Herdi; Taufik, Abun Muhamad (Tirtayasa Journal of International Law, 2024)
The reopening of sea sand export permits has raised concerns among the public after being banned for more than 20 (twenty) years. The government has issued Government Regulation (PP) Number 26 of 2023 concerning Management of Sedimentation Products in the Sea. In this case, the reason for adopting this sand export policy is because it is considered to be important in relation to economic income. So, with the notification that the export of sea sand will be allowed to resume, it continues to reap polemics. The policy of reopening sea sand export permits has caused different reactions from various groups or parties. Those who support it assume that sea sand exports can increase state income through Non-Tax State Revenue (PNBP). Apart from that, the sand from the dredging will be used for development and infrastructure. Those who oppose it believe that the sea sand export policy could have a negative impact on the environmental ecosystem, especially coastal areas and small islands. One of them is sea water abrasion which can have a serious impact on the lives of coastal communities. So, regarding this policy there should be a thorough review. The method used in this research is a normative approach method which is carried out by utilizing descriptive analysis research sources. Dredging sedimentation in the form of sea sand from a business perspective has its own benefits, if used properly, the sea sand export policy can add economic value to a region or country in the form of increasing the country's foreign exchange earnings while still paying attention to the welfare of coastal communities.